Emergence of Carbapenem-Resistant Uropathogenic Escherichia coli (ST405 and ST167) Strains Carrying blaCTX-M-15, blaNDM-5 and Diverse Virulence Factors in Hospitalized Patients - Fatima Mujahid; Muhammad Hidayat Rasool; Muhammad Shafiq; Bilal Aslam; Mohsin Khurshid (Pathogens)
Background: Urinary tract infections (UTIs) are common infectious diseases in hospital settings, and they are frequently caused by uropathogenic Escherichia coli (UPEC). The emergence of carbapenem-resistant (Carb-R) E. coli strains poses a significant threat due to their multidrug resistance and virulence. This study aims to characterize the antimicrobial resistance and virulence profiles of Carb-R UPEC strains isolated from hospitalized patients. Methods: A total of 1100 urine samples were collected from patients in Lahore and Faisalabad, Pakistan, between May 2023 and April 2024. The samples were processed to isolate and identify E. coli using standard microbiological techniques and VITEK®2, followed by amplification of the uidA gene. Antimicrobial susceptibility was evaluated using the Kirby–Bauer disc diffusion method and broth microdilution. Resistance and virulence genes were detected through PCR and DNA sequencing, and sequence typing was performed using MLST. Results: Among the 118 Carb-R UPEC isolates, resistance was most frequently observed against sulfamethoxazole-trimethoprim (96.6%) and doxycycline (96.6%). All of the isolates remained sensitive to colistin and tigecycline. Sequence types ST405 (35.6%) and ST167 (21.2%) were predominant and carried the blaCTX-M-15 and blaNDM-5 genes. The distribution of virulence genes and a variety of antimicrobial resistance genes (ARGs), conferring resistance to aminoglycosides, fluoroquinolones, tetracyclines, and sulfonamides, were observed as specifically linked to certain sequence types. Conclusions: This study provides insights into the molecular epidemiology of carbapenem-resistant Uropathogenic E. coli (Carb-R UPEC) strains and highlights the presence of globally high-risk E. coli clones exhibiting extensive drug resistance phenotypes in Pakistani hospitals. The findings underscore the urgent need for enhanced surveillance and stringent antibiotic stewardship to manage the spread of these highly resistant and virulent strains within hospital settings.